Search for new particles decaying to tt̄ in pp̄ collisions at √s = 1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2000)
The search for narrow-width vector particles was undertaken using 106 pb-1 data from the collider detector at Fermilab. The cross section upper limits for narrow vector resonances decaying to tt are presented. The existence of leptophobic Z boson was not included in the top-color-assisted technicolor model at the 95% confidence level.